PERSEPSI WISATAWAN TERHADAP KUALITAS PELAYANAN PRAMUWISATA LOKAL DI HIDDEN CANYON BEJI GUWANG, KABUPATEN GIANYAR BALI - Maria Purba, Ester Dewi; Oka Karini, Ni Made; Suwena, I Ketut (Jurnal Analisis Pariwisata; Vol 17 No 2 (2017): Jurnal Analisis Pariwisata (Desember 2017), 2017)
Tour guide has a very important role in tourism activities. Can be seen from the function of a tour guide that is as an informers that tourists need in tourist destinations. The purpose of this research is to find out how the tourist perception toward local tour guide’s service quality in Hidden Canyon Beji Guwang, Gianyar regency, Bali. Data collection techniques used in this research are observation, interview, questionnaire and literature study. In determining the sample this research using accidental samplings by distributed questionnaires to 85 respondents. The analysis used is descriptive quantitative. There are two types of respondents domestic tourists amounted to 27 and foreign tourists amounted to 58. This research  uses five variables and consists of seventeen indicators. The result of this research is the perception of tourists as a whole can be concluded, tourist perception toward local tour guide’s service quality in Hidden Canyon Beji Guwang, Gianyar regency, Bali is already very good.